2014
DOI: 10.1055/s-0034-1384639
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Placental Cord Drainage in Management of the Third Stage of Labor: A Multicenter Randomized Controlled Study

Abstract: Active management of the third stage of labor with the cord drainage method significantly reduced postpartum blood loss and the duration of the third stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…While in one international study no significant difference was found in duration of labour between two groups (16) while in another study the third stage of labor was significantly shorter in the cord drainage group than in the control group (3.5 ± 1.9 vs. 7.7 ± 3.4 minutes, respectively; p ˂ 0.001) (17). A study was conducted in India in which two hundred pregnant patients with 37 or more weeks of gestation, with single live fetus in cephalic presentation, who underwent a spontaneous vaginal delivery, were included in the study.…”
Section: Discussionmentioning
confidence: 88%
“…While in one international study no significant difference was found in duration of labour between two groups (16) while in another study the third stage of labor was significantly shorter in the cord drainage group than in the control group (3.5 ± 1.9 vs. 7.7 ± 3.4 minutes, respectively; p ˂ 0.001) (17). A study was conducted in India in which two hundred pregnant patients with 37 or more weeks of gestation, with single live fetus in cephalic presentation, who underwent a spontaneous vaginal delivery, were included in the study.…”
Section: Discussionmentioning
confidence: 88%
“…In the experimental groups, the umbilical cord was unclamped and drained, whereas in the control groups, the cut umbilical cord remained clamped. Uterotonics were used in 4 studies to manage the third stage of labour in both groups 11 , 15 , 16 , 21 . In one study, a uterotonic was used after the expulsion of the placenta 12 .…”
Section: Resultsmentioning
confidence: 99%
“…In one study, a uterotonic was used after the expulsion of the placenta 12 . In 6 studies, instrumental deliveries were excluded 12 , 15 , 16 , 18 , 21 , 22 . Sharma reported the outcomes separately for primigravida and multigravida women 11 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations